Construction supervision - Rounds, Jerald L. 4 0 16; Segner, Robert O.; 5 (Hoboken, New Jersey : John Wiley & Sons, Inc., 2011)
This book covers all supervisory situations one is likely to encounter on a commercial, industrial, or institutional construction project. The book is based upon a very successful Electrical Project Supervision (EPS) training program developed by Rounds and Segner for the National Electrical Contractor?s Association and licensed to several organizations representing other construction sectors. This program has been delivered for over a decade and continues to be delivered to thousands of construction supervisors each year. The program content has consistently received outstanding reviews and evaluations in numerous different venues--;The text is based upon a very successful Electrical Project Supervision (EPS) training program developed by Rounds and Segner for the National Electrical Contractor's Association and licensed to several organizations representing other construction sectors. This program has been delivered for over a decade and continues to be delivered to thousands of construction supervisors each year. The program content has consistently received outstanding reviews and evaluations, throughout the time of its being presented in numerous different venues. This book is written broadly to cover all supervisory situations one is likely to encounter on a commercial, industrial or institutional construction project--
Includes index.
Professional.
Keywords: 2 -- 0; 6; Superintendence. -- Building -- 20; 20; 2